Trabalho e sofrimento psíquico na estratégia saúde da família: uma perspectiva Dejouriana - KATSURAYAMA, Marilise (Universidade Federal do Pará, 2019)
This paper proposes a theoretical construct of "mental suffering" of the worker at the Family Health Strategy (FHS). To this end, we opted for using the theory of the psychodynamics of work from the author Christophe Dejours, seeking a link between theory and practice aspects of the reorientation of primary care model in Brazil. In this sense, the analysis of the workers' mental health employed at the health care forefront appears to be of paramount importance, since it can assist in building evaluation proposals that go beyond traditional and exclusionary perspectives, indicating ways to overcome barriers in public policies, so that it is offered satisfactory service to users in Primary Care. Still, it was possible through this theoretical articulation allow an expansion about the possibilities of talking about work, be heard, to exercise subjective mobilization and seek the transformation of pathogenic conditions, hoping to cause a direct reflection on the organization of work.